Social Support for Exercise and Its Effect on Physical Activity Level among Female Teachers - Mahdi Abdolkarimi; Fatemeh Ayeneh Heydari; Seyedeh Shirin Lotfi; Hadi Eslami (Journal of Social Behavior and Community Health)
Background: Determining the level of physical activity and factors in female teachers can be effective in planning health promotion interventions. Therefore, this study was conducted to determine the level of physical activity and social factors affecting female teachers in Rafsanjan. Methods: in this descriptive study, the level of physical activity and the social factors were examined in 198 female high school teachers in Rafsanjan City in 2019. The International Short Form Physical Activity Questionnaire (IPAQ) was used to determine physical activity levels. Sallis's social support questionnaire for exercise was used to determine the level of social support. Data were analyzed using SPSS 18 and chi-square and Spearman's correlation coefficient. Results: The level of physical activity in female teachers was lower than the recommended level so that only 34.3% had the minimum physical activity at the recommended level. In terms of intensity of physical activity, most physical activities were reported as walking. The physical activity of this group was not statistically significant based on age (p = 0.09), work experience (p = 0.70), level of education (p = 0.28), and income level (p = 0.082). Also, there was a significant correlation between all types of physical activity and social support in all aspects. Conclusion: Providing social support for exercise by family and friends has been identified as an effective physical activity factor. Therefore, it seems necessary to design educational programs to improve teachers' awareness and attitude, emphasizing the creation of a supportive environment by family, friends, and even related organizations.